‘Hoop op iets vaags’: ambiguity, unreliability and indeterminacy in Erwin Mortier’s Marcel (1999) - Mertens, Bram (Taylor & Francis, 2018)
Erwin Mortier’s acclaimed debut novel Marcel, first published nearly twenty years ago, tells the story of a Flemish family haunted by a dark past: the involvement of several members in the wartime collaboration with the German occupier. The novel has usually been read as a narrative of reconciliation, showing the often painful process of successive generations gradually gaining some understanding of the past and coming to terms with it, before being able finally to lay its guilty weight to rest. However, a close reading and historial contextualisation of Marcel reveals a much more complex picture, casting doubt both on the accuracy of the characters’ understanding and the sincerity of their intentions. This article is the first to offer a rival interpretation of Mortier’s novel, proposing that, rather than recognising their guilty past, the characters may be unable or unwilling to acknowledge it as such, and could instead be poised to sow the seeds of its continuation and repetition.